2012
DOI: 10.4236/jis.2012.33028
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Timestamp Discrepancy to Limit Impact of Replay Attacks in MANETs

Abstract: Mobile Ad hoc NETworks (MANETs), characterized by the free move of mobile nodes are more vulnerable to the trivial Denial-of-Service (DoS) attacks such as replay attacks. A replay attacker performs this attack at anytime and anywhere in the network by interception and retransmission of the valid signed messages. Consequently, the MANET performance is severally degraded by the overhead produced by the redundant valid messages. In this paper, we propose an enhancement of timestamp discrepancy used to validate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In summary, physical layer security in UAVs involves employing a combination of different techniques to protect the wireless communication link from unauthorized access, interference, and interception and allows to ensure reliable and secure wireless communication between the UAVs and the GCS. [103] Detection mechanisms and introduction of a timestamp [126,131,132] Unencrypted radio communication Eavesdropping attack [133] Encrypted and authenticated communication [52],…”
Section: Physical Layer Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, physical layer security in UAVs involves employing a combination of different techniques to protect the wireless communication link from unauthorized access, interference, and interception and allows to ensure reliable and secure wireless communication between the UAVs and the GCS. [103] Detection mechanisms and introduction of a timestamp [126,131,132] Unencrypted radio communication Eavesdropping attack [133] Encrypted and authenticated communication [52],…”
Section: Physical Layer Securitymentioning
confidence: 99%
“…They checked if the time profile of the frequency components in the output signal is compatible with the authentication signal. To mitigate the effect of a Replay attack, in [132], the authors introduced a timestamp for each message and suggested a mechanism to estimate the time needed for receiving and validating the message and compare it with the actual time it takes to receive and validate the message by the receiver. If the difference between the estimated and actual time is larger than the threshold, a Replay attack is then declared detected.…”
Section: Physical Layer Securitymentioning
confidence: 99%
“…To prevent an adversary from launching replay attacks using a user's accelerometer readings, similar to [26], an encrypted time-stamped identifier can be generated for each block of the accelerometer measurements. The system will then examine these time-stamped identifiers to ascertain that the measurements are originally collected.…”
Section: User Verification Frameworkmentioning
confidence: 99%
“…Replay attack: To avoid replay attacks in the WMN, a timestamp concept used in [11] is applied in our proposed framework. This timestamp concept permits a receiving mesh node to validate the received signed messages based on the time interval within which it has received the frame.…”
Section: Security Analysismentioning
confidence: 99%